The Perception of Non-English Major Students on Joining English Speaking Club to Support Their Speaking Practice - Rahmawati, Rahmawati; Ayudhia, Honesty Yonanda (Journal of English Language Teaching, 2024)
Speaking is an important but difficult skill to master in English. One of the popular ways for non-English major students at UNP to practice their speaking skill is joining the speech division at UKBA. This research uses descriptive design and qualitative approach by involving 5 non-major English students to be interviewed in depth. The purpose of this study is to find out how students’ perception about the speech division and how activities in this division can support speaking practice. The results of this study indicate that the majority of non-major English students have a positive perception of the speech division. Based on the interviews, the activities in the speech division can support and help students to improve their speaking skills. The speech division also can help students to overcome their problem in speaking. However, in order to be more effective in helping students to learn to speak English, the speech division needs to do some evaluations such as upgrading classroom conditions and developing learning materials such as grammar. In addition, further research is recommended to examine students' perceptions of other divisions in UKBA related to grammar or other English skills.